2022
DOI: 10.1051/0004-6361/202140543
|View full text |Cite
|
Sign up to set email alerts
|

Detecting exoplanets with the false inclusion probability

Abstract: Context. It is common practice to claim the detection of a signal if, for a certain statistical significance metric, the signal significance exceeds a certain threshold fixed in advance. In the context of exoplanet searches in radial velocity data, the most common statistical significance metrics are the Bayes factor and the false alarm probability (FAP). Both criteria have proved useful, but do not directly address whether an exoplanet detection should be claimed. Furthermore, it is unclear which detection th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 97 publications
0
26
0
Order By: Relevance
“…From this model, the posterior distribution for the orbital periods is shown in the top panel of Fig. 3, where the count in each period bin was normalised by the ESS (thus resembling the TIP proposed by Hara et al 2022). The posterior shows two very clear peaks at 5.12 and 11.19 days.…”
Section: Results From the Joint Modelmentioning
confidence: 82%
“…From this model, the posterior distribution for the orbital periods is shown in the top panel of Fig. 3, where the count in each period bin was normalised by the ESS (thus resembling the TIP proposed by Hara et al 2022). The posterior shows two very clear peaks at 5.12 and 11.19 days.…”
Section: Results From the Joint Modelmentioning
confidence: 82%
“…In Gregory (2016), the number of planets is determined by checking that the Bayes factor comparing the n + 1 and n planets model is greater than a certain threshold. The significance of the planet can also be established with the false inclusion probability (FIP; Hara et al 2022), defined as follows. Considering a certain parameter space S (for instance, a period and eccentricity interval), the true inclusion probability (TIP) is the probability of having a planet with orbital elements in S marginalised over the number of planets in the system.…”
Section: Bayesian Approachmentioning
confidence: 99%
“…Gregory 2007b,a;Tuomi 2012;Faria et al 2016). Alternatively, one can use a detection criterion based on Bayesian model averaging (Hara et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested POLYCHORD on the simulated datasets of Nelson et al (2020) and found its results closely matching those of the other nested samplers. In future works we aim to also use other techniques such as Bayesian model averaging, which was recently implemented as a detection criterion for exoplanet detection with radial velocities by Hara et al (2021).…”
Section: Introductionmentioning
confidence: 99%